Talk on Advocacy Skills in Legal Profession - UiTM, Faculty of Law (Faculty of Law, 2020)
On Friday, 73 March 2020, UiTMLaw organised a talk entitled "Advocacy Skills in Legal Profession". The speaker was YBhg. Datuk Dr. Prasad Sandosham Abraham, Adjunct Professor of UiTMLaw. Datuk Dr Prasad talked about advocacy skills in handling clients and cases in open court. Among the objectives of the programme were to enlighten the students on advocacy skills in the legal profession and to motivate them to become good future lawyers. The opening address was delivered by Dean of the Faculty, Associate Professor Dr. Hartini Saripan. The talk was attended by Faculty lecturers and students of Part 7 of LW224 and Part l of LW222 programmes. The advisor of the programme was Dr. Norazlina Abdul Aziz, whilst the director was Dr. Faridah Hussain. The programme was held at Academic 2 Building of UiTM. The Dean of the Law Faculty of UiTM, expressed her gratitute to YBhg. Datuk Dr. Prasad Sandosham Abraham and to the organising committee.